Natural Signs and the Origin of Language - Sukhoverkhov, Anton (Biosemiotics, 2012)
This article considers natural signs and their role in the origin of language. Natural signs, sometimes called primary signs, are connected with their signified by causal relationships, concomitance, or likeliness. And their acquisition is directed by both objective reality and past experience (memory). The discovery and use of natural signs is a required prerequisite of existence for any living systems because they are indispensable to movement, the search for food, regulation, communication, and many other information-related activities. It is argued that the birth of conventional signs, sometimes called secondary signs, was determined by a connotative use of natural signs and that, regulated and maintained by them, human language developed. At the same time, the origin and development of human language presupposes a ‘rational turn’ from the given and external reality of natural signs to the rationally constructed reality of artificial signs and rules that are internally maintained by the subjects’ deliberate activities, and actual and inherited social tradition (social memory). In view of this, language is defined as a dynamic system that must both be natural and artificial, empirical and a priori, inductive and deductive. This bilateral origin and regulation of language is the dual-inference of language.